Pengaruh Cash Holding, Firm Size, dan Kepemilikan Manajerial Terhadap Perataan Laba - Dhiyaa’ Ayu Alisa; Sofyan Hakim; Al Hujjah Asianingrum (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The company’s reported profit can affect the perception and decisions of various parties or stakeholders. By showing stable profits, companies can attract and retain investors. The company’s reported profit can affect the perception and decisions of various parties or stakeholders. By showing stable profits, companies can attract and retain investors.This study aims to obtain empirical evidence on the influence of Cash Holding, Firm Size, and Managerial Ownership on Income Smoothing. The method used in this study is a quantitative research method. The object of this research is consumer non-cyclicals companies listed on the Indonesia Stock Exchange in 2019-2022. The determination of the sample in this study used purposive sampling. The population in this study is 111 companies. There are 16 companies that meet the criteria with a sample of 64. This study uses secondary data obtained through the official website of the Indonesia Stock Exchange. The analysis technique used is binary logistic regression analysis using Eviews12 software. The results of this study show that Cash Holding, Firm Size, and Managerial Ownership simultaneously affect Income Smoothing. Partially, Cash Holding, and Managerial Ownership have an effect on Income Smoothing. Meanwhile, Firm Size partially has no effect on Income Smoothing.